Application of STEAM (Science, Technology, Engineering, Art, Mathematics) Approach in Improving Critical Thinking in Political Science Study Programme Students - Juainah, Norma; Hati, Putri Citra; Dumyati, Dumyati; Yunita, Yunita; Izomiddin, Izomiddin; Nys.Nurlaili, Nys.Nurlaili (Journal of Educational Sciences, 2025)
This study examined the implementation of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach in learning to improve the critical thinking skills of Political Science Study Program students. The interdisciplinary STEAM approach enriches students' thinking processes by integrating scientific logic, creativity, technology, and problem-solving. This research used qualitative methods with data collection techniques in the form of interviews, observations, and documentation of lecturers and students involved in the STEAM-based learning process. This research was conducted in the Politics and Technology course of the class of 2024. The selection of materials and classes was based on the research team's discussions on crucial topics and characteristics relevant to technology utilization. The results showed that applying the STEAM approach encourages students to think analytically, creatively, and reflectively in understanding contemporary political phenomena. Collaboration between science, technology, art, and political analysis elements helps students formulate logical arguments, critically evaluate information, and make decisions based on data and ethics. This research recommends the application of STEAM as an innovative pedagogical strategy in political science curriculum development in the digital era.